Perancangan Aplikasi Kalkulator Menghitung Berat Badan Ideal Berbasis Android - Putri Agustina (Journal of Student Development Information System (JoSDIS), 2022)
Health is a very valuable thing for everyone, but all that can not be realized without if one thing is not met, namely health. The goal to be achieved from the design of this android application is to create an android application system to measure one's ideal body weight, where the input to be filled by the user is to enter height and weight then press the calculation button to get the results. Body mass index (BMI) is one indicator that can be trusted in measuring ideal body fat.